Low oocyte yield during IVF treatment and the risk of a trisomic pregnancy. Issue 6 (December 2017) - Honorato, Talita; Hoek, Annemieke; Henningsen, Anna-Karina; Pinborg, Anja; Lidegaard, Ojvind; Mooij, Thea; van Leeuwen, Floor; Land, Jolande; Groen, Henk; Haadsma, Maaike; ,
Abstract: A low number of antral follicles may result in the selection of suboptimal oocytes that are prone to meiotic errors. The aim of this case-control study was to evaluate women receiving IVF treatment with low oocyte yield (defined as three or fewer oocytes retrieved after ovarian stimulation) who are at an increased risk of a trisomic pregnancy. Data were obtained from Danish and Dutch medical registries between 1983 and 2011. Analyses were carried out in 105 cases and 442 controls matched by age and year of IVF treatment. Cases were women with a trisomic pregnancy (trisomies 13, 18 or 21) resulting from fresh IVF treatment and confirmed by karyotyping. Cases were included regardless of pregnancy outcome. Controls were women with a live born child without a trisomy, resulting from fresh IVF treatment. Low oocyte yield was observed in 6.6% (29/440) of the women, of which 8.4% (7/83) were cases and 6.2% (22/357) controls. Low oocyte yield in IVF treatment was not associated with a higher risk of trisomic pregnancy (OR 1.43, 95% CI 0.64 to 3.19). Stratification for female age, adjustment for history of ovarian surgery, and gonadotrophin-releasing hormone protocol used did not change the results.